A twofold role for global energy gradients in marine biodiversity trends. (16th April 2015) - Valentine, James W.; Jablonski, David; Crame, Alistair
Abstract Explanations for major biodiversity patterns have not achieved a consensus, even for the latitudinal diversity gradient (LDG), but most relate to patterns of solar energy influx into Earth systems, and its effects on temperature (as biochemical activity rates are temperature sensitive) and photosynthesis (which drives nearly all of the productivity that fuels ecosystems). Marine systems break some of the confounding correlations among temperature, latitude and biodiversity that typify the terrestrial systems that have dominated theoretical discussions and large‐scale analyses. High marine diversities occur not only in warm shallow seas where productivity may be either low or high, depending on regional features, but also in very cold deep‐sea regions, indicating that diversity is promoted by stability in temperature and in trophic resources (nutrients and food items), and more specifically by their interaction, rather than by high mean values of either variable. The common association of high diversity with stable but low to moderate annual productivity suggests that ecological specialization underlies the similarly high diversities in the shallow tropics and deep sea. Recent work on shallow‐marine bivalves is consistent with this view of decreasing specialization in less stable habitats. Lower diversities in shallow seas are associated with either high thermal seasonality (chiefly in temperate latitudes) or highly seasonal trophic supplies (at any latitude), which exclude species that are adapted to narrow ranges of those variables.